2016
DOI: 10.1159/000448680
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Neonatal Vitamin D Levels as Measured on Neonatal Dried Blood Spot Samples

Abstract: Background: Vitamin D deficiency is linked to adverse childhood health outcomes, yet data on the distribution and quantifiable determinants of neonatal 25-hydroxyvitamin D3 (25OHD) concentration, a vitamin D biomarker, are limited. Objective: Our aim was to identify determinants of neonatal 25OHD concentration, measured using neonatal dried blood spots (DBS). Methods: A total of 259 ethnically diverse children aged 0-16 years born in Victoria, Australia, were recruited. Data included maternal sun ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
2
10
3
Order By: Relevance
“…Previous prediction models of maternal or neonatal 25(OH)D concentrations found higher prediction than ours, explaining between 40 (20) and 43 % (25) of the total 25(OH)D variance. This difference might relate to the different variables included in the prediction models, distinct study population characteristics, differences in sample sizes and potentially different analytical methods used.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…Previous prediction models of maternal or neonatal 25(OH)D concentrations found higher prediction than ours, explaining between 40 (20) and 43 % (25) of the total 25(OH)D variance. This difference might relate to the different variables included in the prediction models, distinct study population characteristics, differences in sample sizes and potentially different analytical methods used.…”
Section: Discussioncontrasting
confidence: 94%
“…In the Danish population, the 25(OH)D risk loci in GC and 25-hydroxylase (CYP2R1) were associated with serum 25(OH) D concentrations (57) ; and in Hungary, selected SNP (NADSYN1, DHCR7, GC, CYP2R1 and CYP24A1) accounted for 13•1 % of the variance of total 25(OH)D levels (58) . In Australia, the study by Smith et al (25) reported that 5•2 % of the predicted variance in neonatal 25(OH)D from DBS could be explained by infant genetic variants GC (rs2282679) and DHCR7 (rs12785878). Therefore, including information on genetic variance would also have most likely improved our model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mean neonatal vitamin D concentrations from DBSs in this Northern California population, at 80 nmol/L, were on average higher than mean concentrations previously reported in studies using DBS with similar methods in other populations, including other predominantly Caucasian populations that ranged from 29 to 53 nmol/L [Fernell et al, ; McGrath et al, ; Nielsen et al, ; Smith et al, ; Tornhammar et al, ] (Table S5). Additionally, the percentage that met criteria for vitamin D deficiency (23%) or insufficiency (27%) were much lower than in other populations where the majority met these criteria (Table S5).…”
Section: Discussioncontrasting
confidence: 50%